Effect of Sunlight and Shade on N orisoprenoid Levels in Maturing Weisser Riesling and Chenin blanc Grapes and Weisser Riesling Wines - Marais, J.; van Wyk, C.J.; Rapp, A. (South African Journal of Enology and Viticulture, 2017)
The effect of sunlight, shade and degree of ripeness on potentially volatile C13-norisoprenoid concentrations in Weisser Riesling grapes and wines and in Chenin blanc grapes, was investigated. Norisoprenoids were released from their bound forms by acid and enzymatic hydrolysis. With few exceptions, norisoprenoid concentrations were significantly higher in sun-exposed grapes than in shaded grapes. Significant increases in norisoprenoid concentrations were observed with an increase in ripeness. Microclimatic conditions during grape ripening for the production of Weisser Riesling wine with a potential to form lower concentrations of TDN during ageing are proposed.